Foliar stable isotope ratios of carbon and nitrogen in boreal forest plants exposed to long-term pollution from the nickel-copper smelter at Monchegorsk, Russia - Manninen Sirkku; Zverev Vitali; Kozlov Mikhail V (SPRINGER HEIDELBERG, 2022)
Long-term exposure to primary air pollutants, such as sulphur dioxide (SO2) and nitrogen oxides (NOx), alters the structure and functions of forest ecosystems. Many biochemical and biogeochemical processes discriminate against the heavier isotopes in a mixture; thus, the values of delta C-13 and delta N-15 (i.e. the ratio of stable isotopes C-13 to C-12 and that of (15) N to (14) N, respectively) may give insights into changes in ecosystem processes and identify the immediate drivers of these changes. We studied sources of variation in the delta C-13 and delta N-15 values in the foliage of eight boreal forest C3 plants at 10 sites located at the distance of 1-40 km from the Monchegorsk nickel-copper smelter in Russia. From 1939-2019, this smelter emitted over 14,000,000 metric tons (t) of SO2, 250,000 t of metals, primarily nickel and copper, and 140,000 t of NOx. The delta C-13 value in evergreen plants and the delta N-15 value in all plants increased near the smelter independently of the plant mycorrhizal type. We attribute the pollution-related increase in the foliar delta C-13 values of evergreen species mainly to direct effects of SO2 on stomatal conductance, in combination with pollution-related water stress, which jointly override the potential opposite effect of increasing ambient CO2 concentration on delta C-13 values. Stomatal uptake of NOx and root uptake of N-15-enriched organic N compounds and NH4+ may explain the increased foliar delta N-15 values and elevated foliar N concentrations, especially in the evergreen trees (Pinus sylvestris), close to Monchegorsk, where the soil inorganic N supply is reduced due to the impact of long-term SO2 and heavy metal emissions on plant biomass. We conclude that, despite the uncertainties in interpreting delta C-13 and delta N-15 responses to pollution, the Monchegorsk smelter has imposed and still imposes a great impact on C and N cycling in the surrounding N-limited subarctic forest ecosystems.